Tangga-Tangga Pendakian Menuju Ridha Allah dalam Manâzilus-Sâ`irîn ila al-Haqqil-Mubîn Karya Abû Ismâ’îl Al-Harawy: Telaah Pendidikan Sufistik - Manshur, Fadlil Munawwar (Jurnal Penelitian Pendidikan Islam, 2018)
Manâzilus-Sâ`irîn ilâ al-Haqqil-Mubîn is a literary work of tasawuf which contains 100 steps of climbing to the pleasure of Allah which must be passed by man to seek His pleasure. The 100 maqâmât is divided into ten levels, each level there are ten maqam, and each maqam has their own meanings and functions. For the purposes of this study, only 20 ladders were studied due to space and time constraints. The problem in this research is how the researchers interpret and analyze the 20 steps of climbing based on the perspective of Sufism. The theory used in this research is the Islamic literary theory Taufiq Al-Hakim model that says that Islamic literature comes from Allah, dimension of worship, and mission of Islamic da'wah. Islamic literature comes from God because God is the source of all sources. The method of analysis used in this research is tasawuf method and moral method. The tasawuf method is directed at how the reader expresses the elements of the formal object contained in material objects to hone and educate the human soul and heart in worshiping God and in associating with fellow human beings. The moral method is oriented on how literature regulates human experience and assesses the extent to which experience affects its activities, namely the literary activity that produces Islamic literary works containing contents of Sufism that are suitable for the guidance of human life. The superiority of this book is also seen in the unique writing techniques because the author is able to integrate the verses of the Qur'an with his imagination so that this book of tasawuf looks strong from the way of processing the substance and from the side of the moral message. Thus, the teachings of Sufism in this book become more practical and easier to understand by the reader